DEVOLOPING ENGLISH LANGUAGE LEARNERS’ MOTIVATION THROUGH GAMES - Parmankulova, D.R. (Educational Research in Universal Sciences, 2023)
The article reveals the role of games in the process of teaching a foreign language. The use of games in teaching a foreign language develops the skills of dialogue speech and communication, develops the oral initiatives of students and strengthens the natural communicative orientation of the lesson. Many educators and authors assume that when learning through games, students unconsciously memorize new lexical and grammatical material. Thus, the use of games in teaching a foreign language is one of the most effective ways that gives students the opportunity to speak and at the same time motivates them.